Efficacy of stereotactic radiotherapy as salvage treatment for recurrent malignant gliomas - MAYADAĞLI, ALPASLAN; Ekici, Kemal; Ozsekee, Naciye; Mayadagli, Alpaslan; Kocak, Mihriban Erdogan; Olmezoglu, Ali (My University, 2014)
Purpose: To evaluate the efficacy and toxicity of CyberKnife stereotactic radiotherapy (SRT) for recurrent glial tumors previously treated with high-dose radiotherapy.